Obituaries of Female and Male Leaders From 1974 to 2016 Suggest Change in Descriptive but Stability of Prescriptive Gender Stereotypes - Zehnter, Miriam Katharina; Olsen, Jerome; Kirchler, Erich (Frontiers in Psychology, 2018)
We analyzed 1415 newspaper obituaries of female and male leaders from 1974 to 2016, covering a time-span of 42 years, to investigate change in descriptive and prescriptive gender stereotypes. The obituaries’ content was condensed to four categories: agency, competence, and communion were used to investigate changes in descriptive stereotypes. The category likability was used to infer changes in prescriptive stereotypes. Consistent with theories claiming changeability of stereotypes, our results indicate changes in descriptive stereotypes. Female leaders were described as increasingly agentic over time, but not as increasingly competent. Descriptions regarding communion remained unchanged. Simultaneously, our results support theories suggesting stability of stereotypes over time indicating unchanged prescriptive stereotypes. Accordingly, increases in female leaders’ agency were associated with decreases in likability. Overall, our results reconcile divided theories regarding the changeability of gender stereotypes. Furthermore, our results emphasize that research and praxis need to enhance attention on prescriptive stereotypes to facilitate female leadership.